Development of a power meter for a bicycle - SYED FARUQ AL AIDID S AFANDI (2018)
The bicycle is one of the most significant technological invention since the 1800s [1]. The proof is that to this date, people can be seen still riding a bicycle as a mode of transport. Since its existence, people have been improving the bicycle to be more comfortable and efficient for the cyclist. There are also different types of bicycle designed for their specific use and terrain such as the road bicycle, mountain bike, touring bicycle, etc [2]. Other than for transport purposes, bicycles are also used for exercises, recreational activities and sports. There is also a rise of competitive cyclists in various bicycle sport events such as racing, mountain bike trial, and freestyle. For cyclists who race, it is important for them to maximise the energy used while cycling. Therefore, there is a demand for bicycle accessories that increases efficiency and ways to track their performance. This report is a continuation of previous project in developing a power meter that is reliable and accurate while being low cost as compared to the ones that already exists in the market. The aim of this project is to complete the prototype by making the necessary connections and to conduct various tests for its reliability, accuracy and performance. The prototype should also be able to maintain its primary functions and reliability in different conditions such as hot weather or cold situations. This report details the progress of the prototype in two parts: the connections of all the strain gauges in the 10 crank spider arms, and the testing of the prototype under different conditions by applying load on the crank arm at the pedal area. To stimulate hot weather conditions, external heat will be applied.